Research on the hazards of gas leakage and explosion in a full-scale residential building - Chengjun Yue; Li Chen; Zhan Li; Bin Feng; Ruizhi Xu (Defence Technology)
The gas explosion in residential building has always been a highly concerned problem. Explosions in homogeneous mixtures have been extensively studied. However, mixtures are often inhomogeneous in the practical scenarios due to the differences in the densities of methane and air. In order to investigate the effects of gas explosions in inhomogeneous mixtures, experimental studies involving gas leakage and explosion are conducted in a full-scale residential building to reproduce the process of gas explosion. By fitting the dimensionless buoyancy as a function of dimensionless height and dimensionless time, a distribution model of gas in large-scale spaces is established, and the mechanism of inhomogeneous distribution of methane is also be revealed. Furthermore, the stratified reconstruction method (SRM) is introduced for efficiently setting up inhomogeneous concentration fields in FLACS. The simulation results highlight that for the internal overpressure, the distribution of methane has no effect on the first overpressure peak (ΔP1), while it significantly influences the subsequent overpressure peak (ΔP2), and the maximum difference between the overpressure of homogeneous and inhomogeneous distribution is 174.3%. Moreover, the initial concentration distribution also has a certain impact on the external overpressure.